الحركة الإسلامية المعاصرة في العراقالشيخ كمال الدين الطائي1904-1977 (انموذجاً) (University of Mosul-college of Basic Education, 2009)
لم تكن الحركة الإسلامية المعاصرة في العراق وليدة سنوات قليلة ماضية تلك الحركة التي كانت عراقية المنبع والتي حافظ عليها أبناؤها ومنهم الشيخ كمال الدين الطائي، الذي ولد في بغداد 1904، ودرس على يد مجموعة من العلماء ابرزهم والده، تولى عدة وظائف وعمل إماماً وخطيباً في عدة جوامع، اسهم في تأسيس العديد من الجمعيات الدينية والاصطلاحية، اصدر العديد من الصحف الإسلامية وله عدة مؤلفات، كانت له مواقف تجاه القضايا السياسية العراقية والعربية منها ثورتا مايس 1941 وتموز 1958، فضلاً عن مواقفه تجاه القضية الفلسطينية. له مشاركات عدة في مؤتمرات خارجية توفي عام 1977.The Islamic contemporary movement in Iraq hasn't emerged a few years ago. It was originally an Iraqi one. Its members kept it, and among them was Sheikh Kamaliddin At-Taa'i. Sheikh Kamaliddin was born in Baghdad in 1904. He was tutored by a number of clergymen, his father was the most prominent among them. He had various occupations; he worked as an imam and Khatib in many mosques. He contributed to the establishment of many reformative and religious societies. Sheikh Kamaliddin published many Islamic journals and wrote many books. He had his attitude to the Arabic and Iraqi political issues, many Revolution (1941) and July Revolution (1958) were among those issues. Besides, he had his attitude to the Palestinian Affair. He took part in many conferences abroad. Sheikh Kamaliddin died in 1977.